Guramukha Siṅgha Musāfira simaritī grantha - Duggal, Kartar Singh, 1917-; Karanajīta Siṅgha, 1930-; Musāfara, Guramukha Siṅgha, 1899-1976 (Pañjāba Kāṅgarasa, 1977)
Commemoration volume of the life and works of Gurmukh Singh Musafir, 1899-1976, Panjabi litterateur and political leader; includes a selection of his writings (p. 149-231)